2020
DOI: 10.24099/vet.arhiv.0500
|View full text |Cite
|
Sign up to set email alerts
|

The effect of substituting wheat bran with cumin seed meal on laying performance, egg quality characteristics and fatty acid profile in laying hens

Abstract: substituting wheat bran with cumin seed meal on laying performance, egg quality characteristics and fatty acid profile in laying hens. Vet. arhiv 90, 47-56, 2020. ABSTrACT The objective of the present study was to investigate the effect of substituting wheat bran (WB) with cumin seed meal (CSM) on laying performance, egg quality characteristics and egg-yolk fatty acids profile in laying hens. A total of 180 Bovans hens at 55 weeks of age were divided randomly into three treatments. The CSM was incorporated int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…On the other hand, there are insignificant differences among hens in control group and hens fed Nigella sativa meal treatments in the final body weight and total feed intake (Table 3). These enhancements in egg production, egg weight, egg mass and feed conversion under heat stress may be due to nigellone, thymoquinone and phenolic compounds of NSM, these substances of MSN act as anti-stress (Tollba and Hassan, 2003) antioxidant (Mariod et al 2009) antimicrobial and antifungal activity (Rathee et al, 1982;Hanafy and Hatem, 1991;Akhtar et al, 2003;Nickavara et al, 2003) The previous results agreement with Saleh et al, 2020;Aydin et al, 2006 andYalcın et al, 2009 who shown that using different levels of Nigella sativa seed or cumin meal supplementation significantly improved egg production, egg shell thickness of laying hens. Additionally, Zeweil (1996) found that the performance of growing Japanese quail fed diets containing 6.25 or 13.50% NSM were significantly improved as compared to the control one.…”
Section: Introductionsupporting
confidence: 53%
“…On the other hand, there are insignificant differences among hens in control group and hens fed Nigella sativa meal treatments in the final body weight and total feed intake (Table 3). These enhancements in egg production, egg weight, egg mass and feed conversion under heat stress may be due to nigellone, thymoquinone and phenolic compounds of NSM, these substances of MSN act as anti-stress (Tollba and Hassan, 2003) antioxidant (Mariod et al 2009) antimicrobial and antifungal activity (Rathee et al, 1982;Hanafy and Hatem, 1991;Akhtar et al, 2003;Nickavara et al, 2003) The previous results agreement with Saleh et al, 2020;Aydin et al, 2006 andYalcın et al, 2009 who shown that using different levels of Nigella sativa seed or cumin meal supplementation significantly improved egg production, egg shell thickness of laying hens. Additionally, Zeweil (1996) found that the performance of growing Japanese quail fed diets containing 6.25 or 13.50% NSM were significantly improved as compared to the control one.…”
Section: Introductionsupporting
confidence: 53%
“…Mathlouthi et al indicated that dietary supplementation with the essential oils of thyme, sage, and rosemary substantially increased FCR ( p < 0.05) [ 26 ]. The usage of 1.0% oregano in the diet improved egg production and egg weight in hens according to Radwan et al [ 27 ]. Moreover, these medicinal herbs are rich in flavonoids, improving the immune system and generating antibodies [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mango (Emshaw et al., 2012), guava (Lira et al., 2009) and apple (Ayhan et al., 2009) already proved to be cheap and suitable sources of nutrients for poultry. Moreover, extensive studies have been carried out to unveil the potential of varieties of seed meals for poultry including blue lupin (Al‐Sagan et al., 2020), cumin (Saleh et al., 2020), flaxseeds and/or fenugreek seeds (Saleh et al., 2019), pumpkin seed (Martínez et al., 2010), sunflower seed (Rama Rao et al., 2006) and cotton seed (Swiatkiewicz et al, 2016). Variety of herbal plants have also been explored in poultry nutrition to improve productivity, immune response and health status (Aroche et al., 2018); (Haselmeyer et al., 2014); (Saleh et al., 2018); (Navid et al., 2014); (Gerzilov et al., 2015); (Saki et al., 2014).…”
Section: Introductionmentioning
confidence: 99%